Pengaruh Proses Rekrutmen, Penempatan Karyawan dan Pemberian Kompensasi Terhadap Kinerja Karyawan BPR PK Kecamatan Balongan Kabupaten Indramayu - casri, Casriyanti (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This research aims: (a) To determine the implementation of the recruitment process at BPR PK, Balongan District, Indramayu Regency, (b) To determine the implementation of employee placement at BPR PK, Balongan District, Indramayu Regency, (c) To determine the implementation of compensation at BPR PK, Balongan District, Regency. Indramayu, and (d) To determine the influence of the Recruitment Process, Employee Placement and Compensation on Employee Performance at BPR PK, Balongan District, Indramayu Regency. This research is quantitative research using multiple linear regression analysis tools. The population in this study was all employees of BPR PK, Balongan District, Indramayu Regency, totaling 56 people. The sampling technique in this research was purposive sampling with a total of 40 people. The data collection technique was carried out by distributing questionnaires to BPR PK employees, Balongan District, Indramayu Regency. The results of this research show that: (1) the recruitment process variable has a positive and significant effect on employee performance (2) the employee placement variable does not have a significant effect on employee performance (3) the compensation variable has a positive and significant effect on employee performance (4) the recruitment process variable , employee placement and compensation simultaneously have a significant effect on employee performance.